A Giant Left Atrial Myxoma. (21st December 2014) - Zaher, Medhat F.; Bajaj, Sharad; Habib, Mirette; Doss, Emile; Habib, Michael; Bikkina, Mahesh; Shamoon, Fayez; Hoyek, Wissam N.
Abstract : Atrial myxomas are the most common primary cardiac tumors. Patients with left atrial myxomas generally present with mechanical obstruction of blood flow, systemic embolization, and constitutional symptoms. We present a case of an unusually large left atrial myxoma discovered incidentally in a patient with longstanding dyspnea being managed as bronchial asthma.